Recreating the South Sea bubble: Lessons from an experiment in financial history - Giovanni Giusti; Charles Noussair; Hans-Joachim Voth (University of Zurich, Department of Economics, 2014)
Major bubble episodes are rare events. In this paper, we examine what factors might cause some asset price bubbles to become very large. We recreate, in a laboratory setting, some of the specific institutional features investors in the South Sea Company faced in 1720. Several factors have been proposed as potentially contributing to one of the greatest periods of asset overvaluation in history: an intricate debt-for-equity swap, deferred payment for these shares, and the possibility of default on the deferred payments. We consider which aspect might have had the most impact in creating the South Sea bubble. The results of the experiment suggest that the company's attempt to exchange its shares for government debt was the single biggest contributor to the stock price explosion, because of the manner in which the swap affected fundamental value. Issuing new shares with only partial payments required, in conjunction with the debtequity swap, also had a significant effect on the size of the bubble. Limited contract enforcement, on the other hand, does not appear to have contributed significantly.
Keywords: G01; G12; G14; N23; C92; 330; Financial bubbles; experiments; South Sea bubble; risk-shifting; government debt; equity issuance